Exploring primary healthcare practitioners’ experiences regarding the coronavirus disease 2019 (COVID-19) pandemic in KwaZulu-Natal, South Africa - Mchunu, Gugu Gladness; Harris, Orlando; Nxumalo, Celenkosini Thembelenkosini (Primary health care research & development, 2022)
The coronavirus disease 2019 (COVID-19) has spread rapidly around the world since the initial outbreak in Wuhan, China. With the emergence of the Omicron variant, South Africa is presently the epicentre of the COVID-19 pandemic in sub-Saharan Africa. Healthcare workers have been at the forefront of the pandemic in terms of screening, early detection and clinical management of suspected and confirmed COVID-19 cases. Since the beginning of the outbreak, little has been reported on how healthcare workers have experienced the COVID-19 pandemic in South Africa, particularly within a low-income, rural primary care context. The purpose of the present qualitative study design was to explore primary healthcare practitioners' experiences regarding the COVID-19 pandemic at two selected primary healthcare facilities within a low-income rural context in KwaZulu-Natal, South Africa. Data were collected from a purposive sample of 15 participants, which consisted of nurses, physiotherapists, pharmacists, community caregivers, social workers and clinical associates. The participants were both men and women who were all above the age of 20. Data were collected through individual, in-depth face-to-face interviews using a semi-structured interview guide. Audio recordings were transcribed verbatim. Data were analysed manually by thematic analysis following Tech's steps of data analysis. Participants reported personal, occupational and community-related experiences related to the COVID-19 pandemic in South Africa. Personal experiences of COVID-19 yielded superordinate themes of psychological distress, self-stigma, disruption of the social norm, Epiphany and conflict of interest. Occupational experiences yielded superordinate themes of staff infections, COVID-19-related courtesy stigma, resource constraints and poor dissemination of information. Community-related experiences were related to struggles with societal issues, clinician-patient relations and COVID-19 mismanagement of patients. The findings of this study suggest that primary healthcare practitioners' experiences around COVID-19 are attributed to the catastrophic effects of the COVID-19 pandemic with the multitude of psychosocial consequences forming the essence of these experiences. Ensuring availability of reliable sources of information regarding the pandemic as well as psychosocial support could be valuable in helping healthcare workers cope with living and working during the pandemic.